Effectiveness of Eco-Enzyme in Suppressing the Growth of Fusarium sp. on Shallot Plants (Allium cepa) In Vivo - Fitria Sukma; Alfizar; Siti Shofiya Nasution; Muhammad Sayuthi; Hartati Oktarina Oktarina (Talenta Publisher, 2026)
Shallots (Allium ascalonicum L.) are a high-value horticultural commodity in Indonesia, but production often declines due to Fusarium sp., which cause yield losses of up to 80%. Control using synthetic chemical fungicides remains the primary choice for farmers, demanding environmentally friendly alternatives. This study tested the effectiveness of fruit peel eco-enzymes to control of Fusarium sp. in shallot plants. Five levels of eco-enzymes (0, 0.2, 0.6, and 1%) were applied before and after shallot planting. The results showed that eco-enzymes were able to delay the incubation period, reduce disease severity by 30%, and increase the number and weight of bulbs. It can be concluded that eco-enzymes are effective in controlling Fusarium sp., in shallot plants.